2018
DOI: 10.2147/tcrm.s168763
|View full text |Cite
|
Sign up to set email alerts
|

Seventy-two-hour emergency department revisits among adults with chronic diseases: a Saudi Arabian study

Abstract: BackgroundDespite the increase in adult emergency department (ED) utilization in Saudi Arabia, no studies have evaluated the 72-hour revisits. This study estimates the rate of 72-hour ED revisits and identifies its reasons and predictive factors among adults with chronic diseases.Patients and methodsA hospital-based retrospective study that included 24,206 ED discharges for adults with chronic diseases at the adult ED of King Abdulaziz Medical City, Riyadh between September 13, 2015 and July 29, 2017 was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
(27 reference statements)
1
8
1
Order By: Relevance
“…Data were extracted from unified BESTCare database, a large multi-center electronic health information system implemented in MNGHA in 2015 [12]. BESTCare provides patient-centered care through a single electronic health system accessible to health care providers for documentation and updating records and fully accessible to patients to review their medical records electronically [13]. We retrieved data on children’s age, gender, region where a case was diagnosed, and diagnosis weekdays (Yes/No).…”
Section: Methodsmentioning
confidence: 99%
“…Data were extracted from unified BESTCare database, a large multi-center electronic health information system implemented in MNGHA in 2015 [12]. BESTCare provides patient-centered care through a single electronic health system accessible to health care providers for documentation and updating records and fully accessible to patients to review their medical records electronically [13]. We retrieved data on children’s age, gender, region where a case was diagnosed, and diagnosis weekdays (Yes/No).…”
Section: Methodsmentioning
confidence: 99%
“…12,13 Respiratory problems were the frequent presenting complaints in the study conducted in Malaysia and Turkey whereas abdominal pain accounted for the first and second most presenting complaints in different studies done with similar objectives. 7,10,18,20 These complaints are attributed to the next common presenting complaint in our study. Return visits to ED due to previously diagnosed lower respiratory and upper respiratory tract infections among patients could be due to cold season, missed or wrong diagnosis, and short ER stay during the first visit.…”
Section: Discussionmentioning
confidence: 51%
“…Since various factors which can be patientrelated, physician-related, or disease-related contributing to revisits have also been studied, it can reduce the rates if properly addressed. 5 This study may help in improving patient care as the revisit rates are also considered as a tool to assess the quality of care. 6…”
Section: Introductionmentioning
confidence: 99%
“…In addition, disadvantaged groups such as less educated individuals were shown to lack knowledge about their health conditions and ways to manage at home and hence resort to ED as their main source of disease management and education (AL-Jahdali et al 2012). Evidence indicates that elderly tend to use more ED services (Alghanim and Alomar 2015, Pines et al 2011b, Fuda and Immekus 2006, Ahmed et al 2018 while other studies showed that both young and old individuals often use ED services (LaCalle and Rabin 2010). Older patients who tend to have multiple co-morbidities may perceive the hospital ED as a better choice to get more advanced healthcare (Peppe et al 2007).…”
Section: Discussion Of Resultsmentioning
confidence: 99%